DE L’OBJECTIVITÉ ET DE L’EXACTITUDE DE L’INFORMATION MÉDIATIQUE PENDANT LES CAMPAGNES ÉLECTORALES DE 2006, 2011 ET 2018 À KISANGANI.: APPROCHE CRITIQUE DE L’ÉTHIQUE ET DE LA DÉONTOLOGIE JOURNALISTIQUE - Batsu, Henri-Paul IYEL (IJRDO - Journal of Social Science and Humanities Research, 2022)
Medias, in this case television, are the instruments of broad casting information collected, treated, analyzed with objectivity, of news interesting the great public, significant proved above all in electoral period where citizens choose freely leaders able to manage the city or de res publica and to answer to human social needs of the electors. That sacrosanct principle of the journalistic profession has been trampled upon by public and private radios and televisions of Kisangani town in Democratic Republic of Congo that have been substituted to the agents of political propaganda of political, parties and candidates, to walk on the code of good conduct of professional ethics of their profession in electoral period. The present article haminers on the principles of social responsibility of medias in a decisive period of life of a nation young in democracy like in the democratic of Republic of the Congo.